Surface disorder in c-Si induced by swift heavy ions - Bogle, Kashinath A.; Gokhale, Suresh P.; Bhoraskar, Vasant N. (Radiation Effects and Defects in Solids, 2005)
The disorders induced in crystalline silicon (c-Si) through the process of electronic energy loss in the swift heavy ion irradiation were investigated. A number of silicon <100> samples were irradiated with 65 MeV oxygen ions at different fluences, 1x10(13) to 1.5x10(14) ions/cm(2), and characterized by the Raman spectroscopy, the optical reflectivity, the X-ray reflectivity, the atomic force microscopy (AFM) and the X-ray diffraction (XRD) techniques. The intensity, redshift, phonon coherence length and asymmetric broadening associated with the Raman peaks reveal that stressed and disordered lattice zones are produced in the surface region of the irradiated silicon. The average crystallite size, obtained by analyzing Raman spectrum with the phonon confinement model, was very large in the virgin silicon but decreased to <100 nm dimension in the ion irradiated silicon. The results of the X-ray reflectivity, AFM and optical reflectivity of 200-700 nm radiation indicate that the roughness of the silicon surface has enhanced substantially after ion irradiation. The diffusion of oxygen in silicon surface during ion irradiation is evident from the oscillation in the X-ray reflectivity spectrum and the sharp decrease in the reflectivity of 200-400 nm radiation. The rise in temperature, estimated from the heat spike model, was high enough to melt the local silicon surface. The results of XRD indicate that lattice defects have been induced and a new plane <211> has been formed in the silicon <100> after ion irradiation. The results of the present study show that the energy deposited in crystalline silicon through the process of electronic energy loss similar to 0.944 keV/nm per ion is sufficient to induce disorders of appreciable magnitude in the silicon surface even at a fluence of similar to 10(13) ions/cm(2).
Keywords: AFM; crystalline silicon; ion irradiation; optical and X-ray reflectivity; Raman; XRD